Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Section 6.6 - Solving Quadratic Equations by Factoring - Exercise Set - Page 457: 32


The solutions are -4 and -6.

Work Step by Step

(x+3)(x+8)=x $x^{2}$+8x+3x+24=x $x^{2}$+11x+24=x $x^{2}$+11x+24-x=x-x $x^{2}$+10x+24=0 $x^{2}$+6x+4x+24=0 x(x+6)+4(x+6)=0 (x+4)(x+6)=0 x+4=0 x+6=0 x+4-4=0-4 or x+6-6=0-6 x=-4 or x=-6 The solutions are -4 and -6. Check Let x=-4 (x+3)(x+8)=x (-4+3)(-4+8)=-4 -1*4=-4 -4=-4 Let x=-6 (-6+3)(-6+8)=x -3*2=-6 -6=-6
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.